Technical note: Investigating saline water uptake by roots using spectral induced polarization - S. Ehosioke; S. Ehosioke; S. Garré; S. Garré; J. A. Huisman; E. Zimmermann; M. Javaux; M. Javaux; F. Nguyen (Biogeosciences)
Developments in the methods available for root investigation in recent years have enabled many studies to be carried out on roots, which represent the hidden half of the plant. Despite the increased number of studies on roots, there are still knowledge gaps in our understanding of the electromagnetic properties of plant roots, which will be useful to quantify plant properties and monitor plant physiological responses to dynamic environmental factors amidst climate change. In this study, we evaluated the suitability of spectral induced polarization (SIP) for the noninvasive assessment of root activity. We investigated the electrical properties of the primary roots of Brachypodium distachyon L. and Zea mays L. during the uptake of fresh and saline water using SIP measurements in a frequency range from 1 Hz to 45 kHz. The results show that SIP is able to detect the uptake of water and saline water in both species and that their electrical signatures were influenced by the solute concentration. The resistivity and phase response of both species increased with solute concentration until a certain threshold before it decreased. This concentration threshold was much higher in maize than in Brachypodium, which implies that tolerance to salinity varies with species and that maize is more tolerant to salinity than Brachypodium. We conclude that SIP is a useful tool for monitoring root activity and could be adapted for the early detection of salt stress in plants.